Analisis Dampak Perubahan Iklim Terhadap Curah Hujan Berdasarkan Perubahan Zona Agroklimatologi Pada Skala Lokal Politeknik Negeri Lampung - Onny Chrisna Pandu Pradana; Rizka Novi Sesanti (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Pertanian Dharma Wacana, 2018)
Global warming is a trapped occurrence of long-wave solar radiation that emitted back by the earth. The impact of global warming is the occurrence of climate change which will further affect life on the earth. As a result of climate change, there are some agriculture areas that will be drought (getting drier), while in the other areas will get higher rainfall than usual (getting wetter). It can cause farmers to harvest failure and get significant losses. As one of effort to minimize that losses, it is needed the appropriate information about the climate condition (especially on rainfall) of that region in the past and in the present, whether that area is becoming wetter or drier than in previous years. This research aimed to learn the impact of climate change on a local scale in the agriculture area of Lampung State Polytechnic that seen from the foccus area of rainfall, and also to find out whether there has been a change of agroclimatology zone at Lampung Polytechnic agriculture area. This research was conducted in 2016—2017 at Lampung State Polytechnic. In this research, rainfall data that has been collected, analyzed using Oldeman climate classification system for food crops, then analyzed to determine whether that area become wetter or drier than in previous years or constant. The results of this research showed that (1) the impact of climate change at local scale (in Lampung State Polytechnic agriculture area) has been felt that signed from the change of rainfall condition, (2) the current condition in Lampung State Polytechnic agriculture area is wetter than in previous years, and (3) within the last 25 years, agroclimatology zone in the agricultural area of Lampung State Polytechnic has been changed from D3 to C2 zone based on Oldeman climate classification system